Efficacy of Acceptance and Commitment Therapy for Psychological Distress in Patients with Systemic Lupus Erythematous - Zulqaif Akhtar, Saima Majeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Prolonged physical illnesses and resultant health conditions may give rise to mental health problems and psychological distress. Aim: To see the efficacy of Acceptance and Commitment Therapy (ACT) for patients suffering from Systemic Lupus Erythematous. Study Design: Randomized Control Trials. Methodology: A purposive sample of forty adult patients with a mean age of 29.25 years (SD= 6.37) suffering from SLE were enrolled for the research after their signed written informed consent. The sample was drawn from two public hospitals with the prior permission of authorities. Randomized Control Trials were carried out on forty patients with SLE after the random assignment to the experimental group and control group. Pre and post-treatment assessment was completed with the help of a demographic questionnaire, medical history Performa and psychological distress scale. Results: Equal number of men and women were included in the present research. Most of the participants' education level was matric and they belong to middle socioeconomic status. results indicated that ACT significantly contributed to the reduction of psychological distress among the patients of the experimental group p<0.01 i.e. 0.00, (M=19.85, SD=2.27); suggesting a decrease in the level of psychological distress with a large effect size whereas no significant difference in pre and post-test scores of control group p>0.05 i.e. 0.66, was observed. Conclusion: It was concluded that ACT proved an efficacious mode of treatment for psychological distress in patients with SLE. Keywords: Acceptance and Commitment Therapy, psychological Distress and SLE.